Optimalisasi Media Social Instagram Untuk Meningkatkan Brand Awareness Kuotie Nainai - Chandra Kuswoyo; Gabriela Joanna Susanto (Jurnal Riset Bisnis, 2025)
In the era of globalization, the food and beverage industry is experiencing significant growth, with a reported increase of 4.62% in the second quarter of 2023 according to the Central Statistics Agency (BPS). This growth presents substantial market opportunities, particularly in the food sector. Businesses are innovating to attract millennial consumers, but effective marketing strategies are essential for brand recognition. The use of social media is rapidly increasing globally, including in Indonesia, where platforms like Instagram serve as vital marketing communication tools. Instagram's interactive features allow for more personal and direct marketing, making it an effective medium for enhancing brand awareness. This research focuses on Kuotie NaiNai, a food and beverage business facing challenges in maximizing its social media potential. The study employs qualitative descriptive methods to explore how Instagram can be utilized to improve brand awareness through content optimization and paid advertising strategies. Findings indicate that a high engagement rate on Instagram—measured through interactions such as likes and comments—significantly strengthens consumer-brand relationships and enhances brand visibility. Ultimately, this research concludes that effectively leveraging social media can lead to sustainable growth in brand awareness for Kuotie NaiNai.